The effects of lead on the development of somites in chick embryos (Gallus gallus domesticus) under in vitro conditions: a histological study. Issue 3 (20th February 2019) - Amini, Zahra; Mahdavi-Shahri, Naser; Lari, Roya; Behnam Rassouli, Fatemeh
Graphical Abstract: Abstract: Lead (Pb) is one of the most abundant toxic metals in the environment that can cause a variety of harmful effects. During embryonic development of vertebrates, somites are temporary organs that give rise to skeletal muscle, cartilage, tendon, endothelial cells, and dermis. In this study, we investigated the effects of lead on the development of somites and their derivatives in chick embryos under in vitro conditions. For this propose, fertilized eggs of Gallus gallus domesticus were incubated until they reached the stage of 15–20 somites. The somites and notochord were isolated and treated with different concentrations of lead acetate (500, 1000, 2000, and 4000 ng ml −1 ) for 72 h. Our results indicated that high concentrations of lead reduced the nucleus diameter, reduced the synthesis of collagen, inhibited the formation of the cartilage matrix in somite cells, and disturbed the formation and order of myotubes. In conclusion, the results of the current study for the first time indicated the disturbing effects of lead on the development of somites in the chick embryo. Our results revealed that lead disturbed the development of somites in the chick embryo, which suggested that at high concentrations it can cause a serious mortal danger to life.